Brazil's Living Museum : Race, Reform, and Tradition in Bahia - A. Romo, Anadelia (Book collections on Project MUSE., 2010)
Brazil's northeastern state of Bahia has built its economy around attracting international tourists to what is billed as the locus of Afro-Brazilian culture and the epicenter of Brazilian racial harmony. Yet this inclusive ideal has a complicated past. Chronicling the discourse among intellectuals and state officials during the period from the abolition of slavery in 1888 to the start of Brazil's military regime in 1964, Anadelia Romo uncovers how the state's nonwhite majority moved from being a source of embarrassment to being a critical component of Bahia's identity. Romo examines id.